Teaching and learning clinical reasoning skill in undergraduate medical students: A scoping review. - Somayeh Delavari; Farzaneh Barzkar; Remy M J P Rikers; Mohammadreza Pourahmadi; Seyed Kamran Soltani Arabshahi; Abbasali Keshtkar; Helen Dargahi; Minoo Yaghmaei; Alireza Monajemi (PLoS ONE)
Background Clinical reasoning involves the application of knowledge and skills to collect and integrate information, typically to arrive at a diagnosis, implement appropriate interventions, solve clinical problems, and improve the quality of health care and patient outcomes. It is a vital competency that medical students must acquire, as it is considered the heart of medicine. Purpose This scoping review aimed to identify and summarize the existing literature on learning and teaching strategies for improving clinical reasoning skill in undergraduate medical education. Methods We conducted electronic searches in Scopus, PubMed/Medline (NLM), Web of Science (WOS), and ERIC to retrieve articles published between January 1, 2010, and March 23, 2024. We also performed hand searches by scanning the reference lists of included studies and similar reviews and searching three key journals. After removing duplicates, two reviewers independently extracted data from primary articles using a standard data extraction form. The authors used Arksey and O'Malley's framework. Results Among the 46581 retrieved records, 54 full-text articles were included in the present review. We categorized the educational strategies based on their aspects, focus, and purpose. Included studies used various educational strategies for improving clinical reasoning skill in undergraduate medical education by serial cue or whole clinical cases that presented as process-oriented or knowledge-oriented. Conclusion This scoping review investigated various dimensions of educational intervention for improving clinical reasoning skill in undergraduate medical education. There is a need for more precision studies with larger sample sizes, designing studies according to randomized controlled trials standards, determining MCID, or performing meta-analyses to acquire robust and conclusive results.